Transepithelial Photorefractive Keratectomy—Review - Christopher Way; Mohamed Gamal Elghobaier; Mayank A. Nanavaty (Vision, 2024)
The type and nature of refractive surgery procedures has greatly increased over the past few decades, allowing for almost all patient populations to be treated to extremely high satisfaction. Conventional photorefractive keratectomy involves the removal of the corneal epithelium through mechanical debridement or dilute alcohol instillation. An improvement to this method utilises laser epithelial removal in a single-step process termed transepithelial photorefractive keratectomy (transPRK). We explore the history of transPRK from its early adoption as a two-step process, identify different transPRK platforms from major manufacturers, and describe the role of transPRK in the refractive surgery armamentarium. This is a narrative review of the literature. This review finds that TransPRK is a safe and effective procedure that works across a variety of patient populations. Though often not seen as a primary treatment option when compared to other corneal-based procedures that offer a faster and more comfortable recovery, there are many scenarios in which these procedures are not possible. These include, but are not limited to, cases of corneal instability, previous refractive surgery, or transplant where higher-order aberrations can impair vision in a manner not amenable to spectacle or contact lens correction. We discuss refinements to the procedure that would help improve outcomes, including optimising patient discomfort after surgery as well as reducing corneal haze and refractive regression.